CSR Sensemaking: Development within Antenna International - McGhie, Jessica (2012)
This qualitative study focuses on the organisation of Antenna International, who is currently in the process of creating and developing a CSR strategy. This study primarily looks at employee understanding of the concept of CSR, but it also explores the influence of organisational culture as a factor in shaping employees understanding of the term. In analysing a snap shot of the implementation phase, this study identifies how employees use current and historical frames of reference to embed their understanding. The concept of values appears in different contexts throughout the study with evidence of both personal and company values emerging. This study aims to help advance the debate on sensemaking, by analysing a sensemaking period relatively unexplored. It may also help practitioners by presenting ideas and influences which affect employee perception of CSR and subsequent implementation.